2020
DOI: 10.1038/s41467-020-17245-x
|View full text |Cite
|
Sign up to set email alerts
|

Towards brain-tissue-like biomaterials

Abstract: Many biomaterials have been developed which aim to match the elastic modulus of the brain for improved interfacing. However, other properties such as ultimate toughness, tensile strength, poroviscoelastic responses, energy dissipation, conductivity, and mass diffusivity also need to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 39 publications
2
55
0
Order By: Relevance
“…The functional properties of a hydrogel originate from its structure at multiple length scales ( 4 ), with mounting evidence for the importance of physical properties in controlling biological behavior ( 5 7 ). Atomic-scale chemical structure of the polymeric repeating units and pendant functional groups control most of the hydrogel’s chemical properties, and larger-scale features such as nanoscale mesh size, microscopic pores, and the overall polymer concentration primarily affect physical properties such as stiffness and solute transport ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The functional properties of a hydrogel originate from its structure at multiple length scales ( 4 ), with mounting evidence for the importance of physical properties in controlling biological behavior ( 5 7 ). Atomic-scale chemical structure of the polymeric repeating units and pendant functional groups control most of the hydrogel’s chemical properties, and larger-scale features such as nanoscale mesh size, microscopic pores, and the overall polymer concentration primarily affect physical properties such as stiffness and solute transport ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…and Axpe et al.). [ 69,74 ] We suggest that the quick stress relaxation of our gel blends supports growth and migration of neural cultures, even in stiffer gels.…”
Section: Discussionmentioning
confidence: 96%
“…[ 31,32 ] Thus, mimicking the brains ECM in vitro is highly challenging. [ 69 ] Hydrogels feature advantageous properties for the 3D cultivation of neural models, such as the high water content (>90%), potential for functionalization, as well as chemical and physical tunability. [ 28 ] Studies demonstrated that soft hydrogels (<1.5 kPa) support neurite outgrowth [ 39 ] whereas stiffer hydrogels promote astrocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few drawbacks prevent GLIADEL wafers from fulfilling clinical expectations. For instance, the solid wafers suffer from a mechanical mismatch with brain tissue, which incurs risks of neuroinflammatory and neurodegenerative response [9][10][11]. In addition, the solid wafers cannot fully cover the irregular cavity wall and might be easily detached [4].…”
Section: Introductionmentioning
confidence: 99%